MENGUATKAN KEMANDIRIAN BENIH PADI: KARAKTERISTIK DAN KESIAPAN PENANGKAR DI KALIMANTAN BARAT - Didik Saifuddin Anshori; Erlinda Yusinthae; Dewi Kurniati (JURNAL AGRICA, 2026)
The availability of high-quality rice seeds is an important prerequisite in supporting regional food security. However, the production capacity of certified seeds in West Kalimantan is still low compared to the existing rice field requirements. This study aims to analyze the socioeconomic characteristics, land conditions, and readiness of rice seed production facilities as a basis for strengthening the seed system towards regional seed independence. The research was conducted from September to November 2025 in nine districts/cities that are seed production centers using a survey method involving 60 certified rice seed producers. Data were collected through structured questionnaires and field observations, then analyzed descriptively and quantitatively using JASP. The results showed that seed producers were predominantly of productive age (average 51.1 years) with 8.2 years of business experience and relatively small land areas (1.86 ha). Average seed productivity was 3.66 tons/ha with variations between agroecosystems. The availability of agricultural machinery was relatively good, but post-harvest facilities such as drying floors and standard warehouses were still limited. Participation in technical guidance is high, but involvement in cooperatives is still low. Strengthening cooperative institutions, supporting post-harvest infrastructure, and applying location-specific technologies are priority strategies for increasing rice seed self-sufficiency in West Kalimantan.